The role of podcasting in effective curriculum renewal - Ming Nie; Alejandro Armellini; Sue Harrington; Kelly Barklamb; Ray Randall (Association for Learning Technology, 2010)
This paper reports on a case study into the contribution of podcasting to the curriculum transformation of two distance-taught master's programmes. Both programmes attract work-based Occupational Psychology practitioners, most of whom are in full-time employment. Challenges faced by the course team included adding flexibility to the curricula, increasing learner engagement (both with learning materials and feedback) and reducing learner isolation. As part of a coordinated enhancement effort, which included changes to curriculum design and delivery, 59 podcasts were introduced into the curriculum over a 12-month period. Qualitative and quantitative data were gathered from students and staff throughout the study. Action research ensured a regular flow of relevant evidence informing each stage of the renewal process. Evidence suggested that the students' learning experiences improved as a result of four key benefits associated with the integration of podcasting in learning design: personalisation; an additional and different format for providing clear and engaging guidance, support and feedback; increased flexibility and mobility within the curricula; and ‘design once, deliver many times' with minimum adaptation.